Bimbingan Lapangan Dosen Pada Kegiatan KKN Kolaborasi Untuk Mewujudkan Pendidikan Holistik Di Desa Tempeh Kidul - Arijo Isnoer Narjono (AMMA : Jurnal Pengabdian Masyarakat, 2026)
The Kuliah Kerja Nyata (KKN) program is a concrete implementation of the university’s Tri Dharma, particularly in the dimension of community engagement. The success of KKN activities is strongly influenced by the role of field supervising lecturers (Dosen Pembimbing Lapangan – DPL) in guiding, mentoring, building partnerships and motivating students during field implementation. This article aims to describe the role of lecturers’ field supervision in strengthening students’ capacities and its impact on the development of a Holistic and Smart Educational Village in Tempeh Kidul Village. The program was implemented using a Participatory Action Research (PAR) approach, involving students, village officials, educational institutions, and local communities as active partners. The results indicate that lecturers’ field supervision significantly enhanced students’ communication skills, leadership, and program management abilities, while also encouraging community participation in educational activities. The flagship programs included educational film screenings and discussions, Qur’an reading assistance, and basic first aid (P3K) training, which positively contributed to strengthening social values, religious character, and community life skills. This study concludes that lecturers’ field supervision plays a strategic role in ensuring the effectiveness of Collaborative KKN programs and can be replicated in other areas with appropriate contextual adaptations.